Kids making AI: Integrating Machine Learning, Gamification, and Social Context in STEM Education - Sakulkueakulsuk, Bawornsak; Witoon, Siyada; Ngarmkajornwiwat, Potiwat; Pataranutaporn, Pornpen; Surareungchai, Werasak; Pataranutaporn, Pat; Subsoontorn, Pakpoom (2018 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE), 2018)
We present an approach in STEM education at the intersection of machine learning, gamification, and social context based in Thailand. We designed an agricultural based AI challenge that fostered students to learn the process of creating machine learning models in the form of a game with the emphasis on the Four P's of Creative Learning (Projects, Passion, Play, and Peers). Our goal is to come up with an innovative education model that encourages the students to connect the emerging technological solutions such as AI with the pressing realworld problems in the playful environment. We found that machine learning can be used as a tool to successfully conduct interdisciplinary education at the middle school level.